Integrating Collaborative Strategic Reading with Learning Logs: an Alternative Method to Develop Reading Comprehension - Dewi, Nuna Mustikawati; Warsono, Warsono; Faridi, Abdurrahman (Universitas Negeri Semarang, 2018)
The present study was the implementation of Collaborative Strategic Reading (CSR) collaborated with learning logs in reading comprehension teaching and learning process. It was used as another method to help students, cooperatively in small group discussion, and was completed with individual learning logs as a reflection. There were four objectives guiding this study; 1) to explain the way CSR collaborated with learning logs is constructed in reading comprehension teaching and learning process, 2) to explain the CSR collaborated with learning logs enhances students’ reading comprehension, 3) to explain the effectiveness of CSR collaborated with learning logs to improve reading comprehension teaching and learning process, and 4) to describe the students’ perceptions of using CSR collaborate with learning logs in reading comprehension teaching and learning process. This study used action research as a research design. The data were collected by implementing observation, test, and questionnaire. The participants of this study were 39 FITK UIN Walisongo students consisting of 30 female students and 9 male students as the informants,and one college as an observer. The data of this study were classified and analyzed qualitatively and quantitatively. The result of the study showed that there were a significant difference in the result of pre-test and post test. The average achievement in pre-test was 68, 30 (fair category) while in post-test was 75.69 (good category). The implementation of this strategy was positive as it was shown in the students’ perception related to the students’ observation sheets and the teacher’s observation sheet. Therefore, it can be concluded that this strategy, collaborated CSR with learning logs is a wonderful and beneficial alternative method in reading comprehension.